Pengaruh Model Pembelajaran Kooperatif Tipe Think Talk Write terhadap Keterampilan Komunikasi Siswa Kelas V Sekolah Dasar - Citra Lestari; Nurmayani Nurmayani; Ibrahim Gultom; Sorta Simanjuntak; Faisal Faisal (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2024)
The problem in this study is that the learning carried out in grade V SD Negeri 104203 Bandar Khalipah has not fully provided opportunities for students to construct and communicate their ideas, ideas, or opinions orally and in writing, in the social studies content of the material "The Process of the Arrival of Europeans to Indonesia" T.A. 2022/2023. This study aims to determine the effect of the think talk write type cooperative learning model on the communication skills of grade V students of SD Negeri 104203 Bandar Khalipah. This type of research is Quasi Experimental Design using Nonequivalent Control Group Design research design. The subjects in this study were teachers and students. The population in this study was all grade V students of SD Negeri 104203 Bandar Khalipah consisting of class VA 34 students, VB 32 students, and VC 32 students. The sample in this study was the entire VA class as an experimental class of 34 students and the VC class as a control class of 32 students. The data collection instruments used in this study were test and non-test instruments in the form of observation sheets, interview guidelines, and tests. The data analysis technique used in this study is quantitative analysis. The results showed the average score of students' communication skills tests with the think talk write type cooperative model was 17.47 while learning with conventional methods was 9.44. In addition, the results of the calculation of the hypothesis using the t test, obtained tcalculate results = 4.86 > ttable = 1.67, so that Ha is accepted and H0 is rejected. That is, there is a significant positive influence between the use of the think talk write type cooperative model on the communication skills of grade V students of SD Negeri 104203 Bandar Khalipah.